Issues and implications of readiness to change - Yousef Ahmad Alolabi; Kartinah Ayupp; Muneer Al Dwaikat (Administrative Sciences, 2021)
In light of readiness to change, organizational readiness has received little attention with the extensive assessment of individual readiness to change. (1) Background: Therefore, this conceptual paper aims to address the need for change at the organizational level through the lenses of Lewin theory, organizational change theory, and social exchange theory. It will identify issues and implications in readiness to change at the organizational level; (2) Methods: The primary method used in the study was mainly a literature review to add neglected factors driving change such as contextual factors and technology. (3) Results: The paper shows how various players and other determinants of successful change implementation can derail the organization's readiness to embrace change. (4) Conclusions: The paper adds to the available knowledge on how technology is likely to affect organizational willingness to change. The study suggests various solutions that seek to address the issues on organizational readiness to change. Hence, this study may provide organizational managers with takeaway implications on change management for policymakers and practitioners to improve an organization's preparedness towards change implementation.
Keywords: 350; change; change implementation; change management; organizational change; readiness